STRATEGI MENGENAL WARNA MELALUI METODE EKSPERIMEN PADA KELOMPOK KB AISYIYAH BUSTANUL ATHFAL V KEC.KANIGARAN – PROBOLINGGO - Nurus Sya'adah; Warih Windasari, Indriana (Al-ATHFAL: Jurnal Pendidikan Anak, 2023)
The foundation of this research begins with the results of an initial review of information which shows that the ability to understand color through experimental techniques is still lacking. This shows that children are still confused when they receive information about the test combining variations. The essence of this research is to describe the training of educators, the younger generation and children's learning activists through exercises in introducing variety through research techniques. This research utilizes learning space research activities (PTK) which are planned in repeated cycles (cycle I and cycle II). Each cycle consists of 4 stages, namely: structuring, activity, perception and reflection. This research involved 18 children aged 3 to 4 years from KB AISYIYAH BUSTANUL ATHFAL V KEC. KANIGARAN - PROBOLINGGO, 9 of whom were girls and 9 of whom were boys. The information gathering method uses perception and documentation. From the test results, data was obtained about learning the ability to see diversity through preliminary procedures. Exploratory results indicate that viewing diversity through preliminary procedures can prepare the ability to perceive tone. At the pre-action stage, the average achievement level for young people was only 17.4%. The level of completion of initial reading skills in Cycle II was 78%, while the level of completion in Cycle I was 43.4%. The increase from pre-action to cycle I was 17.4% and the increase from cycle I to cycle II was 85%. Based on the data obtained, it can be reasoned that by utilizing color perception techniques through experimental strategies, it can improve the color recognition ability of children in Kb Aisyiyah Bustanul Athfal V Kec.Kanigaran – Probolinggo. Keywords: Ability to Recognize Colors, Early Childhood, Experimental Methods